MUTU GIZI DAN KEAMANAN BEKASAM PRODUK FERMENTASI IKAN TERI SECARA SPONTAN DAN PENAMBAHAN KULTUR MURNI - Uken SS Soetrisno; Rossi RS Apriyantono (Persagi, 2005)
ABSTRACTBackground: Many kind of foods based on fermentation products are used as traditional foods in Indonesia. Such products are tape the sweet fermented cassava as source of carbohydrates, tempe the delicious fermented soybean or other beans as source of protein, dadih the sour fermented buffalo milk as source of calcium and protein, and many others made of animal protein source such as from small fish. Fermentation of foods will increase the nutrient content and absorbability of the nutrient, besides will increase sensoric or acceptability value of the products. Objectives: The study objectives are to evaluate the nutrient quality and sensoric quality of the salt-fermentation product of small fish, so called teri, both using spontaneous fermentation and selected culture-fermentation those producing lactic acid bacteria. Methods: This was a food experimental study to explore the quality improvement of acid bacteria fermentation products using spontaneous or sellected culture on protein source foods. Ingredients were consist of small fish with steam rice at 1 to 1 by weight with addition of salt at 5-6% and fermented spontaneously or with addition of 1% level selected culture, which contain lactic acid producing bacteria. Fermentation were done for 4 to 5 days, depent on the type of culture. Results: Bekasam produced from both type of fermentation had lower protein content due to the addition of rice as carbohydrate source, while ash content became higher due to the addition of NaCl salt. The products had sweet smell besides sour taste due to carbohydrate fermentation which could increase the absorbability of the products especially vitamins and minerals those needed lower pH. Generally, fermented bekasam had higher vitamin content and changed fatty acid composition. Vitamin B12 increased by 2 folds and vitamin A by 3-4 folds, compared with those of fresh small fish. Linoleic acid increased by 2-4 folds followed by decreased of other long chain fatty acids content. Pathogenic microorganisms were still high in raw fermented products, but they were undetected after steaming for 30 minutes. Conclusions: Nutrient contents of the fermentation products, such as vitamin A, B12, linoleic acid were higher than the fresh fish, while the proximate nutrient content depent on the amount of ingredients added as the base component. All fermentation products contained E. coli, Koliform, and Shigella s., these might come from the fish that had been polutted since in the ocean. After steaming or sterillization the product, those pathogen microorganisms were negative or undetected. Based on the nutrient quality, it will be worthwile to develop local food formula using bekasam the fermented teri, for children under five years old. [Penel Gizi Makan 2005,28(1): 31-35] Keywords: fermentation, spontanious, sellected culture, small fish, bekasam.